Pelatihan Massage Endorphine Dan Gym Ball Exercise Bagi Praktik Mandiri Bidan (PMB) Di Ikatan Bidan Indonesia (IBI) Kabupaten Badung - Luh Putu Widiastini; Made Tangkas; I Gusti Agung Manik Karuniadi (Abdi Wiralodra : Jurnal Pengabdian Kepada Masyarakat, 2022)
During pregnancy and childbirth, there can be physical and psychological changes in the mother. These changes can cause anxiety, stress and can eventually lead to depression. The risks that can be caused are the birth of babies with low birth weight (LBW), small head size (microsomia), premature birth, weakening of the baby's immune system, and prolonged labor. The problems that give rise to this idea are the high incidence of anxiety experienced by pregnant and maternity mothers so that it can cause complications for mothers and babies, lack of training and ignorance of the Independent Midwife Practice (PMB) at the Indonesian Midwives Association (IBI) Badung district towards complementary therapies, especially Massage Endorphins. and gymball exercise. The service is carried out by providing 2 training materials, namely Massage Endorphin and gymball exercise which is given to 40 members of the Midwife Independent Practice who are members of the PC IBI Badung Regency which is carried out online.